Research on the Cognitive Diagnosis of Chinese Listening Comprehension Ability Based on the G-DINA Model - Li, Li; An, Yi; Ren, Jie; Wei, Xiaoman (Frontiers in Psychology, 2021)
As a new generation of measurement theory, cognitive diagnosis theory shows significant potential and advantages in educational evaluation in that it combines cognitive process and measurement method. The application of the theory not only reveals learners’ potential characteristics in cognitive processing, but also provides targeted remedies and strategic guidance for individuals. Given the difficulties of traditional assessment models in providing an insightful and fine-grained account for individualized and procedural learning, how to provide personalized learning strategies for learners of Chinese as a second language has been a new goal of teaching and measurement in Chinese listening. This study constructs a cognitive diagnosis model of Chinese listening comprehension for Chinese-as-a-second-language learners through theoretical exploration, model hypotheses, repeated verification and model modification. The results show that the Q-matrix (Q3) constructed by the experts within modification has the highest fitting degree with the empirical data. The parameter recovery rate, the accuracy of the tested attribute or mode and the relative fitting index obtained from the simulation study are consistent with the information extracted from the empirical data. The diagnostic reliability and effectiveness of G-DINA (Generalized Deterministic Input, Noise “and” Gate) are higher than those of DINA, DINO and RRUM. In estimating of the item parameters and subject parameters, the G-DINA model shows good convergence, and the average classification accuracy rate based on attribute level is 0.861.